The role of Whatsapp as a communication media for indekos students - Muhamad Ardan Anuggerah; Farida Nurfalah (International Journal Labs, 2024)
The purpose of this study is to explore the role of WhatsApp as a communication medium for boarding house students. Data collection involved observations, interviews, and documentation with three students living in boarding houses in Cirebon City who regularly use WhatsApp in their daily activities. The results of the research show that WhatsApp has an important role in facilitating the dissemination of information among boarding school students. The frequency, tone, and content of interactions on WhatsApp have an impact on social bonds, social cohesion, sense of belonging, and conflict resolution. In addition, the negative aspects of WhatsApp use, such as miscommunication, digital conflict, or issues of privacy and trust, and how these impact interpersonal relationships among a group living group. Furthermore, it lays the groundwork for future research on the integration of digital tools in improving the quality of life and communication efficiency in residential educational settings, contributing to the broader discourse on technology's impact on education and student well-being.